Implementation of Transformative Islamic Education Change Management in Islamic Boarding Schools - Miftakul Arifin; Binti Maunah; Asrop Syafi'i (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2024)
Changes in educational organizations are common, including in Islamic educational institutions such as Pondok Pesantren Miftahul Ulum Suruhan Lor Bandung. The vision of a kiai to preserve the salaf tradition by utilizing modern tools and keeping up with developments in the era of globalization is realized through change management in several aspects, while still maintaining the local wisdom that characterizes the pesantren. This is done so that the salaf pesantren remains relevant and accepted by modern society. This research aims to: 1) Provide a comprehensive overview of the phases of change that have occurred at Pondok Pesantren Miftahul Ulum Suruhan Lor Bandung, and 2) Describe the changes that have taken place in the pesantren in terms of structure, physical layout, technology, and human resources. This research uses a qualitative approach with a case study design, where the analysis is conducted using deductive analytical logic. The location of this research is Pondok Pesantren Miftahul Ulum Suruhan Lor Bandung. Data were collected through field observations, interviews, and documentation. The obtained data were then reduced, presented, analyzed, and finally concluded.